2018
DOI: 10.3126/njog.v12i1.18978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Domestic Violence Among the Pregnant Women Attending BPKIHS

Abstract: Aims:To find out the prevalence of domestic violence in pregnant women attending Antenatal clinics (ANC) of B. P. Koirala Institute of Health Sciences, a tertiary centre in eastern Nepal.Methods: It was a hospital based cross-sectional study done at antenatal clinics of BPKIHS from 14th March 2015 to 30th August 2015. The total number of recruited antenatal patients was 470. Data were collected by face to face interview via pretested semi-structured questionnaire. Descriptive and inferential statistics were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…World Health Organization's (WHO's) multi-country study revealed that Japanese women experienced the lowest rates of domestic violence while the highest is in Ethiopia, Peru, and Bangladesh. [1] Studies showed that the prevalence of IPV was 30.3% in Tanzania, 53.2% in Nepal, and 67% in Kenya [4][5][6]. A systemic review of African studies showed that intimate partner violence during pregnancy ranged from 2.3% to 57.1 %; most of the studies showed a prevalence of 27% and above [7].…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization's (WHO's) multi-country study revealed that Japanese women experienced the lowest rates of domestic violence while the highest is in Ethiopia, Peru, and Bangladesh. [1] Studies showed that the prevalence of IPV was 30.3% in Tanzania, 53.2% in Nepal, and 67% in Kenya [4][5][6]. A systemic review of African studies showed that intimate partner violence during pregnancy ranged from 2.3% to 57.1 %; most of the studies showed a prevalence of 27% and above [7].…”
Section: Introductionmentioning
confidence: 99%
“…7 Another similar study conducted in the Amhara regional state of Ethiopia shows that the prevalence of domestic violence was 78.0%. 8 This study finding was more as compared to the prevalence of GBV among pregnant women of Paropakar Maternity and Women's hospital, Kathmandu, where 46% experienced GBV. 9 On the other hand, Amnesty International documented domestic violence in Nigeria to be on the increase with up to 33.3% of women experiencing violence in their lifetime.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, it is stated that conducting training workshops and carrying out consultations for women and girls has significantly reduced the number of cases of domestic violence against them (for example, in India) (Nair et al, 2020). But not every social activity can affect the level of domestic violence against pregnant women: for example, the effectiveness of empowerment of pregnant women in the community seems questionable, as it will not affect their ability to confront abusers (Regmi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%